Strategi Pengambilan Keputusan Pengembangan Pendidikan Tinggi Vokasi Kemaritiman - Rufiajid Navy Abritia; F Pambudi Widiatmaka; Yustina Sapan; Nur Rohmah (Sekolah Tinggi Maritim Yogyakarta, 2021)
The demands of changes in the global era have made vocational higher education have a strategic role and are at the forefront in handling the age of the workforce. Vocational higher education is programmed to produce graduates who have mastery of science and technology, are independent, skilled and trained in accordance with the demands of the industrial world or the world of work. The learning outcomes are needed as capital in facing regional and global competition. One of the strategies for decision-making in the development of maritime vocational higher education that was developed to be able to maintain its existence and be more developed in order to produce graduates who are in accordance with the times so that it must have a strategy to achieve it, namely by using the SWOT matrix method approach and the QSPM matrix. Based on the results of the SWOT matrix data processing and the QSPM matrix, it can be concluded that the Director can make a decision to open a new study program, rather than building a new campus which takes longer, with the consequence that new study programs S2 and S3 study in the afternoon while waiting for the construction of a new campus as a the second alternative.